2018
DOI: 10.18517/ijaseit.8.2.4323
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Seismic Behavior of Replaceable Shear Links Connected to Coupling Beam

Abstract: Abstract    A seismic device for steel core frames of high-rise buildings has been developed. The system consists of two concentrically brace frames connected with coupling beams and shear links. The shear link has been designed to yield and dissipate the energy while the coupling beam and other elements of the frames remain elastic. The experimental work had been conducted on a model of halfscale sub-assemblage of core steel frame with its links made in Japan and Indonesia. The result of testing using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Visual inspection after the completion of each testing showed the followings in both end plates of coupling beam and link: (1) no indication of damage on the connecting-surfaces as well as around the perimeter surface of bolt holes, (2) no indication of damage in all bolts, (3) no significant slip occurred on the connected surface, and (4) no permanent distortion observed on coupling beam. Meanwhile, inspection on the RC-wall indicated: (1) a regular but not severe crack pattern, (2) no slip between reinforcing bar and coupling beam to the RC-concrete. Moreover, there was no special technique required during the replacement of link, i.e., removal and installation of links, as shown in Figure 9.…”
Section: Replaceability Of Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection after the completion of each testing showed the followings in both end plates of coupling beam and link: (1) no indication of damage on the connecting-surfaces as well as around the perimeter surface of bolt holes, (2) no indication of damage in all bolts, (3) no significant slip occurred on the connected surface, and (4) no permanent distortion observed on coupling beam. Meanwhile, inspection on the RC-wall indicated: (1) a regular but not severe crack pattern, (2) no slip between reinforcing bar and coupling beam to the RC-concrete. Moreover, there was no special technique required during the replacement of link, i.e., removal and installation of links, as shown in Figure 9.…”
Section: Replaceability Of Linkmentioning
confidence: 99%
“…In this setup, the damage was expected to occur on the shear link only, and the coupling beams as well as other structural elements will not experience yielding. This concept provides easy access and replacement of the link The use of steel coupling beams with replaceable steel shear link in a sub-assembly of a steel-core frame for high-rise buildings has been studied by Kusumastuti, et al [1] and Moestopo, et al [2]. The experimental work showed that the shear link yielded and dissipated energy due to cyclic loading until its maximum strength with its plastic rotation exceeded 0.08 radian, while other elements of core-frame i.e., coupling beam and steel-frame remained elastic.…”
Section: Introductionmentioning
confidence: 99%
“…Pengaku pada link memiliki keterkaitan dengan gaya geser serta rotasi yang terjadi pada link. Link konservatif dengan penambahan pengaku diagonal mampu menahan gaya lateral yang lebih besar apabila dibandingkan dengan link tanpa pengaku diagonal, serta memiliki kemampuan untuk mendisipasi energi dengan baik [14]. Namun pengaplikasian pengaku diagonal pada elemen replaceable link perlu dikaji lebih lanjut agar perilaku link tetap sesuai kaidahnya yaitu mencapai kondisi plastis setelah diberi beban lateral [4].…”
Section: Pendahuluanunclassified